The Korean medicine for aging cohort (KoMAC) study: A protocol for a prospective, multicenter cohort study on healthy aging in the population entering old age in South Korea. - Mi Mi Ko; Seojae Jeon; Wonbae Ha; Young-Eun Kim; So Young Jung; Bo-Young Kim; Myunghwa Kim; Kwang-Ho Choi; Geonhui Kang; So Min Lee; You Mee Ahn; Nahyun Cho; et al. (PLoS ONE)
Background South Korea is anticipated to enter a super-aged society by 2025, necessitating a focus on healthy aging. In Korean medicine (KM), aging and disease susceptibility are individual specific, emphasizing personalized treatments, and many Korean local governments have integrated KM services for elderly people into the public sector. However, there is a notable absence of research incorporating KM to treat older adults. Aim The proposed study aims to examine the comprehensive health profiles of individuals entering old age in rural and urban areas and explore the significant correlations between healthy aging and four key factors: biological, psychological, social, and KM-based phenotype factors. It will also establish a database and blood biobank, serving as a platform for future research to develop a traditional KM-based healthy aging model. Methods A multiple randomized controlled trial design will be adopted in this prospective, multicenter cohort study for the clinical investigation of the markers associated with KM-based healthy aging. The aim is to recruit 1,000 participants who are entering old age from both urban and rural settings for this study, and recruitment began in August 2023 with follow-up surveys planned at one-year intervals. Comprehensive health profiles, including biological, psychological, social, and KM-based phenotype factors, will be developed through the creation of a database, a blood biobank, and multi-omics data. Results In the baseline phase of this study, we will focus on identifying markers for KM-based phenotypes and examining how these phenotypes relate to aging and associated diseases. In the next phase, we will implement interventions tailored to KM-based phenotypes to verify the effects of KM on healthy aging. Ultimately, we intend to develop a KM-based integrated health management model, with further substudies aiming to explore factors related to healthy aging. This protocol was approved by the institutional review board of Wonkwang University Korean Medicine Hospital, Iksan, Republic of Korea (approval number: WKUIOMH-IRB-2023-05) on August 16, 2023 and Jangheung Integrative Medical Hospital (approval number: WKUJIM-202307-001) on August 21, 2023. Recruitment started on August 16, 2023. Conclusion The anticipated results of our study aim to establish personalized preventive and therapeutic interventions for individuals entering old age. Additionally, we seek to offer an KM-based integrated health management model that incorporates comprehensive diagnosis and an integrative medical treatment strategy for healthy aging. Trial registration Clinical Research Information Service: KCT0008863 (registered on October 11, 2023, https://cris.nih.go.kr/cris/search/detailSearch.do/25718).